Evaluation of a photodiode array detector for the verification of peak-homogeneity in high-performance liquid chromatography - Chan, H K; Carr, G P (Journal of pharmaceutical and biomedical analysis, 1990)
Photodiode array liquid chromatography detectors are claimed to have the ability of evaluating the homogeneity of chromatographic peaks and this could provide a very powerful tool in support of method development. However, in pharmaceutical analysis, for this to be of practical value it must be capable of detecting inhomogeneities at low levels. In this paper, a test has been devised to challenge the sensitivity of instruments to this application. The test makes use of mixtures of the similar benzodiazepines temazepam and lormetazepam in a chromatographic system which does not separate them. One instrument has demonstrated the ability to detect levels of just 0.5% w/w of one benzodiazepine in the other. Statistical F-tests and t-tests have been used to demonstrate that non-homogeneities have been detected with a high level of confidence. It is concluded that photodiode array detectors have the potential to evaluate the homogeneity of chromatographic peaks with a high degree of sensitivity. However, most instruments do not realize this potential because their software does not make proper use of all the data available.